Students' Perceptions of Learning Life Skills Through the Teaching Personal and Social Responsibility Model: An Exploratory Study - Jacobs, Jennifer M.; Wright, Paul M.; Richards, K. Andrew R. (Frontiers in Sports and Active Living, 2022)
Purpose Physical education (PE) lags behind community-based sport and physical activity programs in the integration of positive youth development (PYD) principles and practices such as teaching transferable life skills. However, research and educational policy indicates this can and should be part of the PE curriculum. Therefore, there is a significant need to explore students' perceptions and experiences about learning life skills within the PE context. In the current study, an intervention based in a wellestablished PYD approach called Teaching Personal and Social Responsibility (TPSR), was delivered to assess these issues. Methods The current study was conducted in the mid-western U.S. Participants were 122 adolescent students (m = 60, f = 62; M = 12.48 years, SD = 0.97 years) in intervention and control classes. For the intervention, a PE teacher received training on the TPSR approach to promote life skills, while the control teacher received no training and participated in usual practices. Pre- and post-surveys were distributed that examined student perceptions about learning life skills, and supplemental systematic observations were recorded to capture the intervention teacher's fidelity to the TPSR model. Results Results indicated that the intervention group students' perceptions of in-class experiences with life skills such as problem solving, emotional regulation, effort, goal setting, identity experiences, time management, and promoting social norms were enhanced overtime, compared to the control group. Conclusion PE is in a unique position to promote PYD in the school curriculum by teaching of life skills. In this case, participants in the intervention group demonstrated learning personally and socially responsible behaviors across the course of 15 PE lessons. Future research should examine if changed in-class perceptions about life skills can foster use of these skills outside of the PE setting.